Nie traktat, a traktat wierszem... - Gorbaniewska, Natalia (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
Natalia Gorbaniewska, an acclaimed translator of Polish literature into Russian, remembers her first meeting with Miłosz in Paris, and the reading of Traktat poetycki [Treatise on Poetry], which for her became a real translator’s challenge. The memory, in this case, becomes a pretext for a discussion of the genre characteristic of the Treatise, and of the melody of Miłosz’s language and the literary tradition, which makes it possible to understand his poems.